Les noms de Hiroshima mon amour: Hiroshima, Nevers - Boblet, Marie-hélène (Thélème. Revista Complutense de Estudios Franceses, 2007)
The lovers in Hiroshima mon amour do not have any name, but the names of the towns of Nevers in France and Hiroshima in Japan. Duras and Resnais bear witness to the tragedy without gathering evidence. They rather show that nobody can name nor testify what happened at Hiroshima, because we can’t use any point of reference, and meanwhile nobody will never forget it.